Comparison of sous vide cooking method with traditional methods in terms of food quality - Batu, Ali; Batu, Heysem Suat (Bayram Kanca, 2025)
"Sous vide" means "under vacuum" in French and is an important cooking technique widely used in gastronomy today. In this method, the ingredients of the dish to be cooked are first placed in a plastic bag and vacuumed and then placed in a container filled with water with a sous vide device. It is brought to the desired temperature, and the food is kept in the water until it reaches this temperature. Sous vide devices regulate the temperature of the water, keep it exactly constant, when necessary, ensure that the food reaches the desired temperature, and ensure that the food is cooked homogeneously by distributing the heat evenly to every point of the food in the bag. This can only be achieved with slow cookers and special pots that use the slow cooking technique. These products, which are generally powered by electricity, are thermostat-adjusted and operate with temperature and time adjustments. The outer parts of these saucepans are usually metal, and the inner parts are made of clay, ceramic or porcelain, and their transparent lids show the inside. Foods cooked in sous vide are extremely healthy and delicious as a result of long-term cooking, so dishes cooked in these pots are consumed with pleasure. The aim of this article is to focus on the rules of traditional and sous vide cooking methods in food preparation and to emphasize the advantages of the sous vide method over traditional methods and its advantages in terms of producing healthy meals.

"Sous vide", Fransızcada "vakum altında" anlamına gelmektedir ve günümüzde gastronomide yaygın kullanılan önemli bir pişirme tekniğidir. Bu yöntemde, pişirilecek yemeğin malzemeleri öncelikle bir plastik poşete konularak vakumlanır ve ardından sous vide cihazı eşliğinde su dolu bir kabın içine yerleştirilir. İstenilen sıcaklığa getirilip yiyecek bu sıcaklığa ulaşana kadar suyun içinde bekletilir. Sous vide cihazları, suyun sıcaklığını düzenler ve gerektiğinde sabit tutar, yemeğin istenilen sıcaklığa gelmesini sağlar ve ısıyı poşet içindeki gıdanın her noktasına eşit şekilde dağıtarak yemeğin homojen bir şekilde pişmesini sağlar. Bu durum, yalnızca yavaş pişiricilerle ve yavaş pişirme tekniği uygulayan özel tencerelerle sağlanabilir. Genellikle elektrikle çalışan tencereler, termostat ayarlı olup sıcaklık ve zaman ayarlı olarak çalışır. Bu tencerelerin dış kısımları genellikle metaldir ve iç kısımları kil, seramik veya porselenden oluşur, şeffaf kapakları ise içini gösterir. Sous vide ile pişen gıdalar, uzun süre pişirme sonucunda oldukça sağlıklı ve lezzetli olduğundan bu tencerelerde pişirilen yemekler sevilerek tüketilmektedir. Bu makalenin amacı, yemek hazırlama konusunda geleneksel yöntemlerin ve sous vide pişirme yönteminin kurallarına odaklanarak sous vide yönteminin geleneksel yöntemlere göre avantajlarını ve sağlıklı yemek üretebilmek açısından üstünlüklerini vurgulamaktır.
Yemek kalitesi bakımından sous vide pişirme yönteminin geleneksel yöntemlerle karşılaştırılması
Keywords: Sous Vide Cooking; Traditional Cooking; Flavor; Color; Food Quality; Sous Vide Pişirme; Geleneksel Pişirme; Lezzet; Renk; Yemek Kalitesi